Economic and social impacts of multinational corporations in Nigeria - Balogun, Adekunle Daoud (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
Multinational Corporations (MNCs) are commercial ventures without borders. This study analyses the history and operations of MNCs in Nigeria with particular reference to Shell Petroleum Development Company (SPDC) and Chevron Nigeria Limited (CNL). It is an evaluative study using the framework of Michael Todaro and others. It evaluates the positive and negative impacts of MN Cs on Nigeria. It uses data from government documents, periodical reports issued by the respective companies, newspaper reports and other secondary sources. The study found that the MNCs have invested heavily in Nigeria and provided enough benefits in the forms of employment, schools and other infrastructures. However, the study noted adverse consequences resulting from Initial clearing of the mining site, Onshore and offshore Oil spill, Gas flaring, Dredging, and other activities. The companies are aware of environmental pollution and other fall outs but they claim to have taken utmost care in keeping the damages within the tolerable limits. Nevertheless, the damages remain severe and the government of Nigeria apparently has no control in making the MNCs abide by various agreements signed. The study is important and warrants further research using independently derived primary sources